Wall finishes (cement plastered finish) / Muhammad Firdaus Mohd Nawawi - Mohd Nawawi, Muhammad Firdaus (Universiti Teknologi MARA, Perak, 2022)
A surface of the wall is one of the most significant structural parts. The plastering surface has numerous purposes in the performance of a home, and these purposes must be properly comprehended in order to design an appropriate and pleasant structure that also provides privacy and weather protection. This report will go over plastering work for the building's walls. This report was prepared for the development and completion of a surau building and accompanying infrastructure at Kolej Keda, Rimba Taqwa, Sik, 08200 Kedah. The purpose of this study is to examine the building of the plastering wall and how it was carried out. It will concentrate on the entire plastering wall construction procedure. It also investigates the equipment utilized in the ways of plastering wall construction and the time that was spent on the construction. This study will also look at the problem and solution in wall building that will satisfy the plastering wall standards.